Situation Analysis of Health Problems in Depok City in 2021 - Putri, Murti Utami; Adisasmita, Asri C; Djajuli, Hidayat Nuh Ghazali (Jurnal Epidemiologi Kesehatan Indonesia, 2023)
Based on 2021 data, from the results of problem identification, 16 health problems in Depok City were assessed. Maternal mortality was selected as a priority problem with 65 cases of maternal death or 155.58 per 100,000 live births. COVID-19 infection is the most common cause of maternal death. This study aims to provide an overview of maternal death circumstances in Depok because of prioritization following situation analysis of health problems. This situation analysis was conducted in Depok with a quantitative and qualitative approach analyzed using the PAHO-adapted Hanlon involving the participation of 17 respondents from the Health Office and the Head of the PHC in Depok. Primary and secondary quantitative data were collected using questionnaires, the Ministry of Health’s Strategic Plan 2020 2024, Regional Medium-Term Development Plan 2016-2021, and Health Profile 2021. Qualitative data was obtained through interviews with respondents. Maternal mortality got a PAHO score of 42.37. This disease is a priority health problem in Depok. Most pregnant women had a high risk due to a lack of knowledge about pregnancy and a lack of participation in attending pregnancy class programs and pregnancy checks. Lack of family support for the health of pregnant women and there are also challenges in recording and reporting which must be based on an identity card so that cases sometimes do not live in the area but are recorded in the area. There are still some challenges in controlling maternal mortality. Promotive, preventive efforts such as conducting refresher training for health workers and volunteers, counseling, and presenting exciting material in pregnant women’s classes to increase pregnant women’s knowledge and family support. Cross-sector coordination and community leaders must be concerned with all parties to support and assist in screening pregnant women.